20 Efficacy and safety of golimumab induction for moderate to severe ulcerative colitis in the united kingdom: results from the go-colitis. (5th April 2017) - Probert, C; Gaya, D; Hamlin, PJ; Irving, P; Sebastian, S; Gillespie, G; Tate, H; Wheeler, C
Abstract : Background: GO-COLITIS (NCT02092285 ; 2013-004583-56) is a phase 4, multicentre, open-label, single-arm trial in the UK assessing efficacy of golimumab (GLM) in induction and maintenance of clinical response in patients with moderate to severe UC. We report the results of a 6 week interim analysis. Aim: Gather real-world experience of the efficacy and safety of golimumab in an anti-TNF naïve cohort. Method: Anti-TNF naive patients (≥18 year) with UC ≥3 months and with moderate to severe disease were included. Patients received SC GLM on day 0 (200 mg) and day 14 (100 mg) during the 6 week induction phase, followed by GLM 50 or 100 mg 4 weekly in the 48 week maintenance phase. Clinical response and remission were summarised descriptively at the end of week 6. Clinical response was defined as decrease in partial Mayo score of ≥2 points and ≥30% from baseline, plus a decrease in rectal bleeding subscore of ≥1 point or absolute rectal bleeding score ≤1. Results: Overall, 205 patients were enrolled (mean age, 39.3 years). The mean baseline (SD) partial Mayo score was 6.4 (1.4). Clinical responses occurred in 141/205 patients (response rate, 68.8%; 95% CI, 62.0% to 75.1%). Clinical remission occurred in 79/205 patients (remission rate, 38.5%, 95% CI, 31.8% to 45.6%). The mean (SD) change from baseline in partial Mayo score (n=198) was −3.2 (2.4). Serious adverse events (AEs) occurred in 17 (8%) patients: UC flare/worsening was most common (n=11). Conclusions: During the induction phase of GO-COLITIS, 68.8% of patients had a partial Mayo response. AEs were consistent with previous observations.